Molecular Cloning and Characterization of WdPKS1, a Gene Involved in Dihydroxynaphthalene Melanin Biosynthesis and Virulence in Wangiella (Exophiala) dermatitidis - Feng, Bin (American Society for Microbiology, 2001)
1,8-Dihydroxynaphthalene (1,8-DHN) is a fungal polyketide that contributes to virulence when polymerized to 1,8-DHN melanin in the cell walls of Wangiella dermatitidis, an agent of phaeohyphomycosis in humans. To begin a genetic analysis of the initial synthetic steps leading to 1,8-DHN melanin biosynthesis, a 772-bp PCR product was amplified from genomic DNA using primers based on conserved regions of fungal polyketide synthases (Pks) known to produce the first cyclized 1,8-DHN-melanin pathway intermediate, 1,3,6,8-tetrahydroxynaphthalene. The cloned PCR product was then used as a targeting sequence to disrupt the putative polyketide synthase gene, WdPKS1, in W. dermatitidis. The resulting wdpks1Δ disruptants showed no morphological defects other than an albino phenotype and grew at the same rate as their black wild-type parent. Using a marker rescue approach, the intact WdPKS1 gene was then successfully recovered from two plasmids. The WdPKS1 gene was also isolated independently by complementation of the mel3 mutation in an albino mutant of W. dermatitidis using a cosmid library. Sequence analysis substantiated that WdPKS1 encoded a putative polyketide synthase (WdPks1p) in a single open reading frame consisting of three exons separated by two short introns. This conclusion was supported by the identification of highly conserved Pks domains for a β-ketoacyl synthase, an acetyl-malonyl transferase, two acyl carrier proteins, and a thioesterase in the deduced amino acid sequence. Studies using a neutrophil killing assay and a mouse acute-infection model confirmed that all wdpks1Δ strains were less resistant to killing and less virulent, respectively, than their wild-type parent. Reconstitution of 1,8-DHN melanin biosynthesis in a wdpks1Δ strain reestablished its resistance to killing by neutrophils and its ability to cause fatal mouse infections.